Avaliação de mecanismos envolvidos na gastroproteção induzida pelo extrato etanólico da entrecasca da Caesalpinia pyramidalis Tul. - Diniz, Polyana Borges França (2014)
Caesalpinia pyramidalis, is an endemic plant from the North east of Brazil which present scientifically proven anti-inflamatory, antinociceptive, and gastroprotective activities. This work aimed at evaluating the gastroprotective effect of the extract of Caesalpinia pyramidalis (EECp) bark in acute gastric ulcers induced by ethanol in Wistar rats. The ulcered animals were treated with a dose of 100mg/kg of EECp and L-NAME (nitric acid blocker) and Propargylglycine (hydrogen sulfide blocker). It was evaluated, in all treatments, the role of the gas mediators such as nitric oxide (NO) and hydrogen sulfide (H2S) and also the participation of mast cells and molecules involved in the anti-inflamatory process as iNOS and citocin IL-4. It was observed in the NO evaluation that the treatment with L-NAME was not able to revert the inhibitory effect of EECp on the ulcers induced by ethanol, showing that the EECp does not operate via NO. However, the H2S can operate in the gastro protection of the EECp as its block hindered the gastroprotective effect on the ulcers induced by ethanol. In order to evaluate the mast cells, histological cuts were made with toluidine blue/alcian blue/safranine where different mast cells phenotypes were observed. In all treatments a prevalence of mucous mast cells was observed. The techniques of immunofluorescence and flow cytometry were used to evaluate IL-4 and iNOS. The ulcered animals treated with EECp presented high expression of IL-4 and low expression of iNOS, suggesting an anti-inflammatory activity of EECp. In conclusion, the gastroprotective effect of EECp and its action mechanism are related to H2S in diminishing the oxidative stress, the induced NO synthase, and the positive immunomodulatory effect for IL-4, with the diminution of mucous mast cells during the inflammatory process.